2007
DOI: 10.2224/sbp.2007.35.9.1173
|View full text |Cite
|
Sign up to set email alerts
|

Who Gives What to Charity? Characteristics Affecting Donation Behavior

Abstract: Giving to charities takes two major forms: time and money. In this study the authors explored whether donors/nondonors can be distinguished using demographic, socioeconomic, and psychographic variables suggested by literature across disciplines. Data were collected through a large-scale telephone survey in Taiwan. The results indicate that determinants affecting volunteering are mostly intrinsic while those for monetary donations are mostly extrinsic. Additionally, educational attainment and income are useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
3
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 0 publications
7
106
3
11
Order By: Relevance
“…Braus (1994), for example, found that men made larger average donations and tend to respond favorably to raffle tickets and shop counter collections. Other studies found that women gave more frequently and are found to donate more of both money and time (Lee & Chang, 2007;Dvorak & Toubman, 2013;Roberts & Roberts, 2012;Schlegelmilch et al, 1997;Simmons & Emanuele, 2007). Moreover, there is also the argument that these issues are blurred by the fact that these respondents could be influenced by the social desirability factors (Bekkers & Wiepking, 2011;Louie & Obermiller, 2000).…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Braus (1994), for example, found that men made larger average donations and tend to respond favorably to raffle tickets and shop counter collections. Other studies found that women gave more frequently and are found to donate more of both money and time (Lee & Chang, 2007;Dvorak & Toubman, 2013;Roberts & Roberts, 2012;Schlegelmilch et al, 1997;Simmons & Emanuele, 2007). Moreover, there is also the argument that these issues are blurred by the fact that these respondents could be influenced by the social desirability factors (Bekkers & Wiepking, 2011;Louie & Obermiller, 2000).…”
Section: Demographic Factorsmentioning
confidence: 99%
“…However, generally, there is some consistency that individuals appear to become more involved with charities through increased donation behavior as they age (e.g. Bennett, 2003Bennett, , 2011Grace & Griffin, 2006;Lee & Chang, 2007;Simmons & Emanuele, 2007). Indeed, Sze, Gyurak, Goodkind, & Levenson (2012) found that emotional empathy and altruistic behavior increase with an individual's age; and they suggest that this is likely due to a greater reactivity to the need to help others.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…With the final item, we measure how interested the study participants are to work professionally for an NPO. Volunteering, donating, and becoming a member are traditional activities associated with the nonprofit sector (Freeman 1997;García-Mainar and Marcuello 2007;Lee and Chang 2007;Tchirhart 2006). Professional paid work might not be as prevalent an activity as donating or volunteering, but it is a relevant part of the NPO ecosystem nonetheless (Leete 2006;Onyx and Maclean 1996), which is why we include it as an attitudinal dimension.…”
Section: Operationalizing Attitudes Towards Nposmentioning
confidence: 99%
“…Conversely, recruiting volunteers and obtaining donations are seen nowadays as vital activities for every organization pursuing its mission in a responsible way. Current research claims that time and money go hand in hand (Clain and Zech 1999;Lee and Chang 2007;Bekkers and Theo 2008), and that they are complementary from the viewpoint of charities and their resource management strategies (Bekkers 2010). It is believed that time and money, are therefore required to be considered in tandem by charitable institutions.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the impact of the donor's volunteerism into donations' practices is conducted, which aims to uncover the relationship between volunteerism in different donors and their donations practices. On this issue different studies have attempted to illustrate this relationship (Lee and Chang 2007;Peloza, Hudson et al 2009) and its usefulness for organizations (Abreu 2012). The key research question that is elicited here addresses the impact of different drivers of pro-social behavior on volunteerism.…”
Section: Introductionmentioning
confidence: 99%